Biocompatible and Electroconductive Nanocomposite Scaffolds with Improved Piezoelectric Response for Bone Tissue Engineering - Sana Por Hajrezaei; Masoumeh Haghbin Nazarpak; Shahriar Hojjati Emami; Elham Shahryari (International Journal of Polymer Science)
Electroactive scaffolds are relatively new tools in tissue engineering that open new avenue in repairing damaged soft and hard tissues. These scaffolds can induce electrical signaling while providing an ECM-like microenvironment. However, low biocompatibility and lack of biodegradability of piezoelectric and conductive polymers limits their clinical translation. In the current study, we have developed highly biocompatible, electroconductive nanofibrous scaffolds based on poly-L-lactic acid/polyaniline/carbon nanotube (PLLA/polyaniline/CNT). Physical and chemical properties of fabricated scaffolds were tested using various techniques. Biological characteristics of the scaffolds are also examined to check cellular attachment as well as differentiation of cultured (progenitor) cells. Scaffolds were optimized to direct osteogenic differentiation of mesenchymal stem cells. Such scaffolds can offer new strategies for the regeneration of damaged/lost bone.